Evaluation of Serodia Myco II particle agglutination test for detecting Mycoplasma pneumoniae antibody: comparison with mu-capture ELISA and indirect immunofluorescence. Issue 2 (February 1990) - Barker, C E; Sillis, M; Wreghitt, T G
Abstract : The Serodia Myco II particle agglutination test, which the manufacturers claim exclusively detects IgM antibody, was compared with two IgM-specific tests, a mu-capture ELISA, and indirect immunofluorescence for their ability to detect recent Mycoplasma pneumoniae infection. In general there was good agreement among the three tests, all three having similar sensitivity. One hundred and nine (78%) of serum samples gave concordant results in all three assays. Several sera gave positive particle agglutination titres, however, while being negative by the two other assays, and the Serodia Myco II test may not be as specific for detecting M pneumoniae IgM as the other two tests. While the Serodia Myco II test may be a good screening assay, it is unlikely to be a definitive test for M pneumoniae IgM, but may be better than the complement fixation test, particularly in younger patients in whom M pneumoniae IgM is found more frequently.